2004
DOI: 10.1590/s0104-66322004000300004
|View full text |Cite
|
Sign up to set email alerts
|

Niobium carbide synthesis by solid-gas reaction using a rotating cylinder reactor

Abstract: -A rotating cylinder reactor was designed for the synthesis of niobium carbide powders at 1173 K. Niobium carbide, NbC, was prepared by carbothermal reduction starting from commercial niobium pentoxide powders. The reactor was heated using a custom-made, two-part, hinged, electric furnace with programmable temperature control. The design and operational details of the reactor are presented. The longitudinal temperature gradient inside the reactor was determined. Total reaction time was monitored by a gas chrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 9 publications
(10 reference statements)
1
3
0
Order By: Relevance
“…Figure 1 presents the XRD pattern for the 5% and 10% copper added NbC (NbC, 44355-ICSD). The reaction products presented complete conversion to carbides with cubic structure, as indicated by other authors 26,27 . With higher dopant content (Figure 2, top) new peaks arise at θ=43.28° e θ=50.56° which are characteristic of metallic copper (*) (43493-ICSD) which forms a single copper phase.…”
Section: Methodssupporting
confidence: 81%
“…Figure 1 presents the XRD pattern for the 5% and 10% copper added NbC (NbC, 44355-ICSD). The reaction products presented complete conversion to carbides with cubic structure, as indicated by other authors 26,27 . With higher dopant content (Figure 2, top) new peaks arise at θ=43.28° e θ=50.56° which are characteristic of metallic copper (*) (43493-ICSD) which forms a single copper phase.…”
Section: Methodssupporting
confidence: 81%
“…Synthesis of carbides and nitrides of these elements has been carried out by a wide variety of methods that can be classified as (i) thermal treatments, 8–25 (ii) plasma chemical processes, 26 (iii) mechanochemical synthesis, 27,28 and (iv) electrochemical synthesis 29 . However, few reports have been published on the synthesis of carbonitride phases, and only niobium carbonitride has received more attention due to its superconducting properties 26,30,31 .…”
Section: Introductionmentioning
confidence: 99%
“…The mean particle size of Nb 4 AlC 3 was measured to be 0.91 μm, and the specific surface area of powder was tested to be 10.2 m 2 /g. In a previous report, NbC particles with the diameter of 27 nm had the specific surface area of only 11.0 m 2 /g 30 . The high specific surface area of the present Nb 4 AlC 3 powder may be ascribed to the existence of numerous delaminations in the fragmented grains.…”
Section: Resultsmentioning
confidence: 46%
“…In a previous report, NbC particles with the diameter of 27 nm had the specific surface area of only 11.0 m 2 /g. 30 The high specific surface area of the present Nb 4 AlC 3 powder may be ascribed to the existence of numerous delaminations in the fragmented grains. Additionally, it was found that other than the elements of Nb, Al, and C, oxygen was detected in the milled powder by EDS analysis (not shown for brevity).…”
Section: Resultsmentioning
confidence: 79%